Bacteria and yeast microbiota in milk kefir grains from different Italian regions. (August 2015) - Garofalo, Cristiana; Osimani, Andrea; Milanović, Vesna; Aquilanti, Lucia; De Filippis, Francesca; Stellato, Giuseppina; Di Mauro, Simone; Turchetti, Benedetta; Buzzini, Pietro; Ercolini, Danilo; Clementi, Francesca
Abstract: Kefir grains are a unique symbiotic association of different microrganisms, mainly lactic acid bacteria, yeasts and occasionally acetic acid bacteria, cohabiting in a natural polysaccharide and a protein matrix. The microbial composition of kefir grains can be considered as extremely variable since it is strongly influenced by the geographical origin of the grains and by the sub-culturing method used. The aim of this study was to elucidate the bacteria and yeast species occurring in milk kefir grains collected in some Italian regions by combining the results of scanning electron microscopy analysis, viable counts on selective culture media, PCR-DGGE and pyrosequencing. The main bacterial species found was Lactobacillus kefiranofaciens while Dekkera anomala was the predominant yeast. The presence of sub-dominant species ascribed to Streptococcus thermophilus, Lactococcus lactis and Acetobacter genera was also highlighted. In addition, Lc. lactis, Enterococcus sp., Bacillus sp., Acetobacter fabarum, Acetobacter lovaniensis and Acetobacter orientalis were identified as part of the cultivable community. This work further confirms both the importance of combining culture-independent and culture-dependent approaches to study microbial diversity in food and how the combination of multiple 16S rRNA gene targets strengthens taxonomic identification using sequence-based identification approaches. Highlights: The microbiota of Italian milk kefir grains was investigated. A combination of culture-independent and culture-dependent methods was applied. The predominant species were Lactobacillus kefiranofaciens and Dekkera anomala . The presence of sub-dominant species was also highlighted.